Program and abstracts of the 52nd annual meeting of the American Society of Tropical Medicine and Hygiene (American Society of Tropical Medicine and Hygiene, 2003)
The publication contains the program and abstracts of a conference that focused on tropical medicine and hygiene. Intended for professional public.
American journal of tropical medicine and hygiene, ISSN 0002-9637 Volume 69, number 3, supplementum September 2003
Keywords: kongresy jako téma; Hygiene; tropické lékařství; hygiena; Tropical Medicine; Congresses as Topic; cestovní a tropická medicína